An die Wertschöpfungskette gelegt: Die finanzgetriebene Restrukturierung in der deutschen Automobilzulieferindustrie und ihr Scheitern - Scheuplein, Christoph (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
In the past decade, there has been a wave of acquisitions in the German automotive supplier industry by private equity. The financial investors seemed to reorganize the sector but this process was abruptly halted because of the world economic crisis from 2008. A number of companies high above average owned by private equity fell into insolvency and, overall, the power structures in the value chain of the industry remained stable. This is illustrated by means of empirical data of 163 corporate takeovers. The example illustrates that the financial market capitalism is not able to establish a stable production regime yet.